Beyond Regimes : China and India Compared. - Prasenjit, Duara; Perry, Elizabeth J. (Boston : BRILL, 2018)
"Contemporary China and India have been powerfully shaped by trans- and subnational forces. This volume approaches China and India via a strategy of "convergent comparison," exploring local and global influences through a focus on labor relations; legal reform and rights protest; public goods provision; and transnational migration and investment"--Provided by publisher.
4. State-Embedded Villages: Rural Protests and Rights Awareness in India and China -- PART III: PUBLIC GOODS PROVISION -- 5. Parallel Trajectories: The Development of the Welfare State in China and India -- 6. Higher Education Reform in China and India: The Role of the State -- PART IV: TRANSNATIONAL MIGRATION AND INVESTMENT -- 7. Rescaling State-Society Relations in China and India -- 8. Foreign Direct Investment in China and India: History, Economics, and Politics -- Appendix: India-China Timeline, 1947-2016
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Comparative government; Transnationalism; Industrial relations -- China; Industrial relations -- India; Civil rights -- China; Civil rights -- India; Comparative industrial relations; China -- Politics and government; India -- Politics and government; China -- Economic conditions; India -- Economic conditions; Transnationalisme; Relations industrielles -- Chine; Relations industrielles -- Inde; Relations industrielles comparées.; Chine -- Politique et gouvernement; Inde -- Politique et gouvernement; Chine -- Conditions économiques.; Inde -- Conditions économiques.; HISTORY / Asia / China; Civil rights; Comparative government; Comparative industrial relations; Economic history; Industrial relations; Politics and government; Transnationalism; China; India